New adverse coronary events in valve-in-valve TAVR and native TAVR—A 2-year matched cohort - Koren, Ofir; Patel, Vivek; Naami, Robert; Naami, Edmund; Nagasaka, Takashi; Shechter, Alon; Natanzon, Sharon Shalom; Kohan, Siamak; Allison, Zev; Lerner, Addee; Cheng, Daniel Eugene; Chakravarty, Tarun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective To assess the incidence of new adverse coronary events (NACE) following transcatheter aortic valve replacement (TAVR) and valve-in-valve TAVR (ViV-TAVR). Background ViV-TAVR is an accepted treatment for degenerative prostheses among patients with high surgical-risk. TAVR studies have suggested an increased risk of coronary artery obstruction and flow stasis causing thrombus formation. Whether contemporary ViV-TAVR is associated with higher rate of coronary events compared to TAVR is unknown. Methods We used data from 1,224 TAVR patients between 2016 and 2021. We propensity-matched patients following ViV-TAVR and TAVR by significant predictors to overcome confounders in patients' baseline characteristics and procedural factors. Results The matched population included 129 patients in each group. In line with prior reports, there was a higher in-hospital coronary artery obstruction rate with ViV-TAVR (3.1 vs. 1.6%; p = 0.23). Despite this, 2-year cumulative NACE rates were similar between groups (4.7 vs. 6.2%, respectively, p = 0.79), with no difference between its components: myocardial infarction (MI) (p = 0.210), unplanned coronary catheterization (p = 0.477), or coronary artery bypass grafting (CABG) (p = 0.998). Moreover, hypoattenuated leaflets thickening (HALT) at 30-day CT was observed in nearly a quarter of the patients with no difference between groups (23.9 vs. 23.1%, HR 1.02, 95% CI 0.50–1.28, p = 0.872). The progression rate of the coronary artery calcium score (CACS), assessed in a third of patients, was similar between groups (p log-rank = 0.468, 95% CI 0.12–1.24). Low coronary artery height was an unfavorable predictor for in-hospital coronary obstruction and 2-year NACE rate (HR 1.20 and HR 1.25, p = 0.001 and p < 0.0001, respectively). Conclusion At 2-year follow-up, ViV-TAVR was not associated with a higher rate of myocardial infarction, unplanned catheterization, coronary artery bypass grafting, or hypoattenuated leaflet thickening.